Optimasi Tegangan-Daya Reaktif Pada Penyulang Rayap Menggunakan Alternating Direct Methods of Multipliers - Zebua, Osea; Ginarsa, I Made (Jurusan Teknik Elektro Fakultas Teknik Universitas Mataram, 2025)
The varying levels of voltage and reactive power can affect the amount of active power losses in the power distribution network. Therefore, optimization of voltage and reactive power values ​​needs to be done to reduce the amount of active power losses while improving the voltage profile at each bus. This paper presents the optimization of voltage and reactive power in the distribution network using the alternating direct method of multipliers (ADMM) algorithm. Optimization with the ADMM algorithm is carried out by separating the optimization of continuous variables and discrete/integer variables for each iteration and implemented by simulation using MATLAB software. The case study used is the Rayap feeder distribution network at the Metro substation, Lampung Province. The simulation results show that optimization of voltage and reactive power can reduce active power losses from 37.44 kW before optimization to 34.78 kW and improve the voltage profile at each bus from a minimum voltage value of 0.9713 per unit before optimization to 0.9734 per unit. The optimal tap position of the load tap changer obtained is 17 while the capacity position of the two capacitor banks is 400 kVAR each.